Value of Pi - Handous, Abdelhakim (Journal of Asian Business Strategy, 2011)
Traditional methods of calculating the value of Pi are approximate. This article demonstrates that there is an accurate method for calculating its value to 16 significant digits based on the performance of a computer program in Turbo C 2.0 including formulas resulting from the combination of mathematical properties of the circle and the theorem of Pythagoras.